Ensuring integrity and security of medical image transmission in IoMT using highly imperceptible and robust watermarking approach - Priyanka Singh; K. Jyothsna Devi; Tousif Khan Nizami; Choudhary Shyam Prakash; Hiren Kumar Thakkar; Syed Abid Hussain; Saurav Mallik (Scientific Reports)
Abstract With the technological revolution, the Internet of medical things (IoMT) has developed to be of immense benefit. In IoMT, medical images and patients’ data are widely transmitted through private/public network. An ideal transmission should not jeopardize the security, confidentiality, authenticity, authorization, or integrity of medical data/images. To ensure effective transmission and address the aforementioned issues, this paper proposes a blind region based medical image watermarking approach where a medical image is partitioned into region of interest (ROI) and region of non-interest (RONI). To ensure ROI intergrity, localized tamper detection and recovery bits (LTDRB) are generated. For precise diagnosis, patient’s electronic health record (EHR) and LTDRB are embedded in RoNI using hybrid DWT-SVD. No embedding is done in RoI to maintain its integrity and high visual quality. To ensure the security and confidentiality of EHR, a novel encryption scheme using Magic Square technique with low computational cost is proposed . Experimental results demonstrates that the proposed scheme provides high imperceptibility (Avg. PSNR>55 dB, SSIM $$≈$$ ≈ 1 and BER $$≈ 0$$ ≈ 0 ), robustness, security at low computational cost and high accuracy in tamper detection and recovery. A comparative study with some of the latest related research shows that the proposed scheme provides imperceptibility and robustness at par. However, the proposed scheme shows superior performance by providing higher EHR security at low computational cost and higher accuracy in ROI tamper detection and recovery, which other schemes have overlooked.